Exploring the association between recent concussion, subconcussive impacts and depressive symptoms in male Australian Football players. Issue 1 (8th March 2020) - Harris, Sarah Ann; Chivers, Paola T; McIntyre, Fleur L; Piggott, Ben; Bulsara, Max; Farringdon, Fiona H
Abstract : Objectives: To explore the association between depressive symptoms and recent head-related trauma (diagnosed concussion, subconcussive impacts) in semiprofessional male Australian Football (AF) players. Methods: Sixty-nine semiprofessional male players from a West Australian Football League (WAFL) club participated in the study (Mage =21.81, SD=2.91 years). Depressive symptoms were measured using the Centre for Epidemiological Studies Depression Scale. Injuries and potential confounding variables (eg, pre-existing mental health condition; alcohol or drug hangovers; experiencing a stressful event) were self-reported anonymously using the WAFL Injury Report Survey. Both tools were administered every 2-weeks over the first 22-weeks of the WAFL season. Controlling for potential confounding variables and other injuries, a repeated measures generalised estimating equations model assessed the risk of clinically relevant depressive symptoms occurring, when diagnosed concussion or subconcussive impacts were experienced. Results: A total of 10 concussions and 183 subconcussive impacts were reported. Players who experienced a concussion were almost nine times more likely to experience clinically relevant depressive symptoms (OR 8.88, 95% CI 2.65 to 29.77, p<0.001). Although elevated, depressive symptoms following subconcussive impacts were not statistically significant (OR 1.13, 95% CI 0.67 to 1.92, p=0.641). Conclusion: These findings indicate that semiprofessional AF athletes may be at risk of experiencing depressive symptoms after concussion. Severity (concussion vs subconcussive impacts) and dose (number of impacts) appear to have an important relationship with depressive symptom outcomes in this cohort and should be considered for further research and management of player welfare.